Islamic Man: Deep Insights from Monzer Kahf - Netta Agusti (JURNAL ILMIAH SYI'AR, 2021)
This paper aims to discuss how the contemporary economic figure Monzer Kahf thinks about Islamic economics. This paper provides an overview of how the discussion of Kahf's theory of an economic system that works based on Islamic teachings. The basic assumption of the theory built by Kahf is a critique of the economic man that applies to conventional economics, Kahf provides a form of thought as a substitute for this concept known as the concept of Islamic man. On that basis, Kahf developed the theory of consumption and production, the teachings of the commandment of zakat, the prohibition of usury and the idea of al-qirad as an alternative to the interest system.